2019
DOI: 10.1007/978-3-030-20671-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroethics of Augmenting Human Memory Using Wearable Pervasive and Ubiquitous Technologies

Abstract: Neuroethics is a field of study that deals with the ethical and moral issues in neuroscience. Memory augmentation approaches and technologies, is rooted in the broad field of neuroscience and brings with it its own set of ethical issues. Memory augmentation is a new emergent field, where the well-being of humans is augmented using pervasive and ubiquitous technologies. Augmenting Alzheimer and dementia patients' memory with wearable pervasive computing technologies like lifelogging shows a promising memory imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…It has been shown that technology can help maintain independence and improve quality of life. Some examples of how technology can support older adults in living independently are: cognitive problems detection [4], tracking systems for dementia patients [5,6], training cognitive functions such as short-term memory [7], or augmenting human memory [8]. The interdisciplinary field of designing technology and environments for independent living and social participation of older persons in good health, comfort, and safety is known as gerontechnology [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that technology can help maintain independence and improve quality of life. Some examples of how technology can support older adults in living independently are: cognitive problems detection [4], tracking systems for dementia patients [5,6], training cognitive functions such as short-term memory [7], or augmenting human memory [8]. The interdisciplinary field of designing technology and environments for independent living and social participation of older persons in good health, comfort, and safety is known as gerontechnology [9].…”
Section: Introductionmentioning
confidence: 99%